Ultrastructure of the cyanobacterium Nostoc muscorum and exploitation of the culture for hydrogen production - Shah, V; Garg, N; Madamwar, D (Folia microbiologica, 2003)
An effect of various physico-chemical parameters on nitrogenase-catalyzed oxygen-free hydrogen production by Nostoc muscorum was demonstrated. More hydrogen was produced in the light than in the dark. Optimum temperature was 40 degrees C Various sugars increased hydrogen production whereas on easily metabolized nitrogen sources it was inhibited. The production was sensitive to salinity and Fe3+, Cu2+, Zn2+ and Ni2+ ions. Ultrastructural study revealed many electron-dense layers outside the cell-wall area that have not been observed earlier.
Keywords: Carbon; dusík; Culture Media; Microscopy, Electron; Cyanobacteria; světlo; elektronová mikroskopie; peroxid vodíku; Temperature; Nitrogenase; sinice; Hydrogen Peroxide; Light; uhlík; Nitrogen; teplota; nitrogenasa; kultivační média